The Codebreakers war: David Kahn, Macmillan, the government, and the making of a cryptologic history masterpiece. Issue 3 (4th May 2023) - Sherman, David
Abstract: David Kahn's The Codebreakers, published in 1967, is the first modern comprehensive history of cryptology. Based on extensive research, including interviews with former government cryptologists in the United States and Europe, Kahn's volume blazed a trail that numerous historians would follow. It also attracted the attention of intelligence officials in Washington and London, who sought to excise or edit passages in the book. In one of these, Kahn made but agreed to remove a claim that during World War II the Allies had broken the supposedly invulnerable Enigma, a feat that would remain secret until the following decade.